2012
DOI: 10.1186/1471-2474-13-237
|View full text |Cite
|
Sign up to set email alerts
|

Functional exercise after total hip replacement (FEATHER) a randomised control trial

Abstract: BackgroundProlonged physical impairments in range of movement, postural stability and walking speed are commonly reported following total hip replacement (THR). It is unclear from the current body of evidence what kind of exercises should be performed to maximize patient function and quality of life.Methods/designThis will be a single blind multi centre randomized control trial with two arms. Seventy subjects post primary total hip arthroplasty will be randomized into either an experimental group (n=35), or to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 16 publications
0
17
0
10
Order By: Relevance
“…Additionally, the present study indicated all patients had poor result after THR at the 4 th and 10 th postoperative day. These findings were supported by Monaghan, Grant, Hing, and Cusack (2012) who stated that THR patients experienced pain, physical impairment, reduced range of motion and reduced muscle strength persisting for one year [54] . The findings of the study also come in agreement with Singh and Lewallen (2010) who reported that patients had moderate to severe pain and activity limitation (defined as a limitation in 3 or more activities) following THR surgery [55] .…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, the present study indicated all patients had poor result after THR at the 4 th and 10 th postoperative day. These findings were supported by Monaghan, Grant, Hing, and Cusack (2012) who stated that THR patients experienced pain, physical impairment, reduced range of motion and reduced muscle strength persisting for one year [54] . The findings of the study also come in agreement with Singh and Lewallen (2010) who reported that patients had moderate to severe pain and activity limitation (defined as a limitation in 3 or more activities) following THR surgery [55] .…”
Section: Discussionmentioning
confidence: 62%
“…A continuación, en el cuadro 20.1, se describen distintos procedimientos o técni-cas indicadas en la fisioterapia de prótesis de cadera (Grotle et al, 2010;Monaghan et al, 2012).…”
Section: Tratamiento Rehabilitador De La Prótesis De Caderaunclassified
“…However, postoperative residual dissatisfaction is linked to complications due to comorbitities, such as unbalanced (Giaquinto, Ciotola, & Margutti, 2007), muscle weakness (Bhave et al, 2007), limitations in activities (Singh & Lewallen, 2010) and maintain abnormal gait (Foucher et al, 2007). These functional limitations are associated with preoperative dysfunction and will be long-lasting persistence in patients after the surgery (Monaghan, Grant, Hing, & Cusack, 2012;van Dijk et al, 2010). Surgical approach and bedrest following an orthopedic surgery will compromise additional muscle weakness and decreasing aerobic capacity (Convertino, Bloomfield, & Greenleaf, 1997;Meneghini, Pagnano, Trousdale, & Hozack, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The further changes, that may cause balance and gait problems in THA patients, are damage to proprioceptors due to excise or capsule released from the hip, altered unequal leg length and weight bearing (Bohannon, 1995;Nallegowda et al, 2003). It is necessary to do physical rehabilitation exercise to re-train for balance, gait, and activities of daily living in postoperative care (Bhave et al, 2007;Monaghan et al, 2012;Nallegowda et al, 2003).…”
Section: Introductionmentioning
confidence: 99%